2005
DOI: 10.1073/pnas.0409370102
|View full text |Cite
|
Sign up to set email alerts
|

Cellular transformation by the MSP58 oncogene is inhibited by its physical interaction with the PTEN tumor suppressor

Abstract: The PTEN (phosphatase and tensin homologue) tumor suppressor protein contains a single catalytic domain with both lipid and protein phosphatase activities. The remaining C-terminal half of the PTEN protein plays a role in its stability and is mutated in many clinical cancer samples. Here, we report that the PTEN C-terminal domain physically interacts with the forkhead-associated domain of the oncogenic MSP58 protein and that this interaction requires PTEN Thr-366. We further show that while MSP58 transforms Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 18 publications
0
104
0
1
Order By: Relevance
“…9 Further, despite early studies proposing that PTEN was exclusively cytoplasmic, recent reports have demonstrated that nuclear PTEN has important tumor-suppressive functions beyond its lipid phosphatase activity, 11,12,32 and some observations support the notion that PTEN can also localize to mitochondria and regulate apoptosis. 13,14 These findings highlight the possibility that different tumor-suppressive mechanisms of PTEN may occur in well-defined cellular compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Further, despite early studies proposing that PTEN was exclusively cytoplasmic, recent reports have demonstrated that nuclear PTEN has important tumor-suppressive functions beyond its lipid phosphatase activity, 11,12,32 and some observations support the notion that PTEN can also localize to mitochondria and regulate apoptosis. 13,14 These findings highlight the possibility that different tumor-suppressive mechanisms of PTEN may occur in well-defined cellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…These include a poorly characterized protein phosphatase activity and proposed nonenzymatic mechanisms such as interaction with other proteins. [7][8][9] Recent advances have also proved the importance of PTEN subcellular localization. Localized PTEN activity appears to establish PIP3 signal gradients that regulate cell polarity during motility.…”
mentioning
confidence: 99%
“…PTEN has been shown to interact with many proteins in the nucleus including MSP58, which is a proto-oncogene and can transform cells in PTENdeficient mice. 66 Clearly, the nuclear activities of PTEN are diverse. Continued elucidation of the roles of PTEN in the nucleus will help us to unravel the various functions of this essential tumor suppressor gene.…”
Section: Pseudo-pten and Other Oncogenes Decoys For Mirnasmentioning
confidence: 99%
“…Additional studies showed that, in the nucleus, MSP58 could function to regulate transcription through its interactions with the transcription factors Daxx, STRA13, and the RNA-binding protein FMR (Lin et al, 2002;Ivanova et al, 2005;Davidovic et al, 2006). A study showed that TOJ3, the quail homologue of MSP58, displayed transformation activity in juntransformed fibroblasts (Bader et al, 2001), whereas the tumor suppressor gene PTEN could suppress its transforming activity (Okumura et al, 2005). In addition, our previous studies demonstrated that MSP58 interacted with N-myc downstream regulated gene 2 (Ndrg2) in the nucleus, which exerted important functions on cell differentiation and tumor proliferation (Zhang et al, 2007).…”
mentioning
confidence: 99%